Departmental leadership: Engaging others in mentorship - Stockham, Marcia G. (My University, 2008)
This paper presents one chairperson’s experience using a formalized, structured mentoring program to foster success of newly-hired, pre-tenured faculty. A description of the specific model is offered, as well as an outline of benefits, challenges, and suggestions for department heads interested in starting a similar program.
Keywords: Mentors; Mentoring; Department head